The long run relationship between private consumption and wealth: common and idiosyncratic effects - Christian Dreger; Hans-Eggert Reimers (European University Viadrina, Department of Business Administration and Economics, 2011)
We investigate the long run relationship between private consumption, disposable income and wealth approximated by equity and house price indices for a panel of 15 industrialized countries. Consumption, income and wealth are cointegrated in their common components. The impact of house prices exceeds the effect arising from equity wealth. The long run vector is broadly in line with the life cycle permanent income hypothesis, if house prices are allowed to enter the relationship. At the idiosyncratic level, a long run equilibrium is detected between consumption and income, i.e. the wealth variable can be excluded. The income elasticity in the idiosyncratic relationship is significantly less than unity. Hence, the presence of wealth effects in consumption equations arises from the international integration of asset markets and points to the relevance of risk sharing activities of agents. Without sufficient opportunities, an increase in national saving rates would be expected, leading to a lower path of private consumption expenditures.
Keywords: C23; E21; E32; G15; 330; permanent income hypothesis; panel cointegration; wealth effects; Einkommenshypothese; Vermögenseffekt; Gesamtwirtschaftlicher Konsum; Verfügbares Einkommen; Vermögen; Schätzung; Industriestaaten